Advertising to children concepts and controversies - Macklin, M. Carole; Carlson, Les.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
Advertising to Children stimulates and informs the debate on the ethics and effectiveness of marketing to children. The research tackles a wide range of issues including smoking and alcohol consumption.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Television advertising and children -- United States; Advertising and children -- United States; Electronic books